Promotion and Policy Influence Prices on Consumer Purchase Decision on Football Cafe Lubukpakam - Nurul Syafrida (Institute of Computer Science (IOCS), 2018)
This research was conducted at the Football Cafe Lubukpakam the which is a culinary company in the field of food and beverages. The research objective is to analyze and Determine the effect of promotion and price on purchasing decisions. This type of research uses associative research, the population is consumers who come to visit and buy at the Football Cafe Lubukpakam in March 2019 as many as 2,325 consumers, random sampling is Slovin formula so that the number of samples is 95 respondents. Data sources using primary data, the data collection techniques using literature studies, questionnaires and observations. Data analysis using multiple linear regression techniques, classic test Assumptions and hypothesis testing.Based on the results of the study Showed that partially and simultaneously promotion and price had a positive and significant effect on consumer purchasing decisions at Football Cafe Lubukpakam. R square coefficient value (R2) Showed that consumer's purchasing decisions can be explained by promotions and prices by 90.60% and the remaining 9.4% can be explained by other variables not Examined.